Screening rice genetic resources for major diseases of uplands and quality traits of resistant donors - D. MAITI, N. BHATTACHARYA and S. B. LODH2, J.S. CHAUHANI, M. VARIAR, V. D. SHUKLA, (Indian Phytopathology, 2002)
Of 93 rice accessions (43 exotic and 50 indigenous) screened for leaf blast (Pyricularia grisea [Magnaporthe grisea]) resistance during 1994-95 in upland nurseries in India, Arroz Dos Indios, CNA 108-8-42, CNA 4136, IRAT 267 and Akashi were highly resistant. Fifty seven accessions exhibited moderate resistance. All exotic accessions except Laxmijata and GS 529 were resistant. Among indigenous accessions, only Pallavi besides Akashi was resistant and 19 were moderately resistant. About half (53%) ofthe 59 accessions evaluated for reaction to leaf brown spot (Drechslera oryzae [Cochliobolus miyabeanus]) possessed resistance or moderate resistance. The accessions Lohana 1, Kalamkata and Rangi were highly resistant. Accessions Areba, Aditya, Pallaviand Dular were resistant or moderately resistant to both leaf blast and brown spot. Of the 5 highly blast resistant accessions, Arroz Dos Indios also possessed high milling out-turn, head rice, long kernel, high water uptake and volume expansion, while Akashi had high water uptake, kernel linear elongation and intermediate amylose content. Accessions Jhillidhan, Lohana 1 and Rangi had high kernel linear elongation and a high level of resistance to brown spot. Such donors could prove invaluable in the hybridization programme to improve rice quality and disease resistance.